Teacher's experiences in PBL: implications for practice. (3rd March 2016) - Alves, Anabela C.; Sousa, Rui M.; Fernandes, Sandra; Cardoso, Elisabete; Carvalho, Maria Alice; Figueiredo, Jorge; Pereira, Rui M.S.
Abstract : Project-Based Learning (PBL) has been implemented in the first year of the Industrial Engineering and Management programme at the University of Minho, Portugal, since 2004/2005. The purpose of this paper is to analyse and discuss teachers' experiences in PBL in this programme and to explore its implications for student learning and for teaching practices in higher education. For data collection, the research method used was written narratives to these teachers, at the end of the PBL semester. Findings suggest that teachers express a positive view of PBL as a learning approach. They identify student motivation and engagement, along with a better understanding of the application of concepts in real-life situations, as important outcomes of the project for students. Besides this, teachers also highlight the importance of the development of transversal skills by students throughout the project. Recommendations for future work and implications for practice will also be discussed.